Copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material and preparation method thereof

Through the preparation of copper-cobalt sulfide/poly3,4-ethylenedioxythiophene composite electrode material, oxidation polymerization is performed using copper-cobalt sulfide carrier and ammonium persulfate oxidant, poly3,4-ethylenedioxythiophene is easily agglomerated and The problem of lower specific capacitors achieves high specific capacitors and excellent cycle stability, which is suitable for supercapacitors.

CN116013700BInactive Publication Date: 2025-01-14FUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211182582.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Poly3,4-ethylenedioxythiophene, as a supercapacitor electrode material, has problems such as easy agglomeration and lower specific capacitance, which limits its application in supercapacitors.

Method used

Copper cobalt sulfide/poly3,4-ethylenedioxythiophene composite electrode material was used to prepare copper cobalt sulfide/3,4-ethylenedioxythiophene composite material by solvothermal method, and use copper cobalt sulfide support and ammonium persulfate The oxidant undergoes oxidation polymerization reaction, and the resulting poly3,4-ethylenedioxythiophene is firmly coated on the surface of copper-cobalt sulfide, preventing agglomeration and increasing the specific capacitance.

Benefits of technology

High specific capacitance and excellent electrochemical cycle stability are achieved. When the charge and discharge current density is 1 A/g, 2 A/g, 4 A/g and 8 A/g, the specific capacitance is 198~223 F/, respectively. g, 182~204 F/g, 171~189 F/g and 162~178 F/g, the capacitance retention rate reached 82.4~87.1% after 2000 cycles, significantly improving the economic and social benefits of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116013700B_ABST
    Figure CN116013700B_ABST
Patent Text Reader

Abstract

The invention discloses a copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material and a preparation method thereof, and belongs to the technical field of supercapacitor electrode material preparation. The composite electrode material is first prepared by a solvent thermal method using copper nitrate trihydrate, cobalt nitrate hexahydrate, thioacetamide and 3,4-ethylenedioxythiophene as raw materials, and then using the obtained copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material as a carrier, 3,4-ethylenedioxythiophene as a monomer, and ammonium persulfate as an oxidant, and prepared by oxidative polymerization. The composite electrode material prepared by the present invention has a higher specific capacitance and a relatively excellent cycle stability, and is mainly used to make electrodes for supercapacitors, with significant economic and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of supercapacitor electrode material preparation, and specifically relates to a copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite electrode material and a preparation method thereof. Background Art

[0002] Poly (3,4-ethylenedioxythiophene) (PEDOT) has excellent conductivity, ductility and thermal stability, and is a very promising supercapacitor electrode material. However, PEDOT has disadvantages such as high molecular weight and easy agglomeration. Therefore, its redox reaction rate is slow, and during the charge and discharge process, when ions are embedded in / out of PEDOT, the structure of PEDOT is easily destroyed. All these lead to low energy density and reduced specific capacitance of PEDOT electrode materials, which limits the application of PEDOT in supercapacitors. Summary of the invention

[0003] The present invention aims at the problems of easy agglomeration and low specific capacitance of poly (3,4-ethylenedioxythiophene) as a supercapacitor electrode material, and provides a copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite electrode material and a preparation method thereof. The composite electrode material prepared by the present invention has high specific capacitance and excellent cycle stability.

[0004] To achieve the above object, the present invention adopts the following technical solution:

[0005] A copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material is prepared by first using copper nitrate trihydrate, cobalt nitrate hexahydrate, thioacetamide and 3,4-ethylenedioxythiophene as raw materials through a solvent thermal method, and then using the obtained copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material as a carrier, 3,4-ethylenedioxythiophene as a monomer, and ammonium persulfate as an oxidant to obtain the obtained material through an oxidative polymerization reaction.

[0006] The preparation of the composite electrode material comprises the following steps:

[0007] (1) 0.5-1 g of copper nitrate trihydrate, 1-3 g of cobalt nitrate hexahydrate, 0.5-2 g of thioacetamide and 1-2 g of 3,4-ethylenedioxythiophene were added to 300-500 mL of a mixed solvent, and the mixture was first mechanically stirred for 30-60 min at room temperature, and then ultrasonically mixed for 30-60 min. The resulting mixture was then transferred to a high-pressure reactor and reacted at 160-200 °C for 8-12 h. The mixture was then cooled, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material.

[0008] (2) 1-3 g of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in step (1) is added to 50-100 mL of deionized water, and mechanically stirred for 30-60 min at room temperature, and then ultrasonically dispersed for 1-2 h. Then, 1-6 g of 3,4-ethylenedioxythiophene is added, and mechanically stirred for 30-60 min, and then ultrasonically dispersed for 1-2 h. Then, 50-100 mL of ammonium persulfate hydrochloric acid solution is added dropwise to the mixed dispersion at a rate of 10-20 drops / min, and mechanically stirred for 12-36 h at room temperature. After precipitation with methanol, filtration, washing, and vacuum drying, the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material is obtained.

[0009] Furthermore, the mixed solvent in step (1) is prepared by mixing ethylene glycol and ethanol in a volume ratio of 1:2 to 2:1.

[0010] Furthermore, in the ammonium persulfate hydrochloric acid solution of step (2), the concentration of ammonium persulfate is 0.5 mol / L, the concentration of hydrochloric acid is 0.2 mol / L, and the solvent is deionized water.

[0011] The significant advantages of the present invention are:

[0012] (1) The present invention adds 3,4-ethylenedioxythiophene to the reaction system of copper cobalt sulfide, and through the metal-sulfur bond between the copper and cobalt atoms in the copper cobalt sulfide and the sulfur atoms of 3,4-ethylenedioxythiophene, 3,4-ethylenedioxythiophene is firmly attached to the inner and outer surfaces of the copper cobalt sulfide. The obtained copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material is then added to the polymerization reaction system of poly 3,4-ethylenedioxythiophene, and the generated poly 3,4-ethylenedioxythiophene can be further firmly coated on the surface of copper cobalt sulfide. Therefore, the supporting effect of the copper cobalt sulfide carrier can be used to improve the cyclic stability of poly 3,4-ethylenedioxythiophene.

[0013] (2) The copper cobalt sulfide prepared by the present invention has a hollow microsphere structure with a thin shell, and ions can diffuse quickly to all electrochemical reaction active sites. At the same time, when the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material is added to the polymerization reaction system of poly (3,4-ethylenedioxythiophene), the generated poly (3,4-ethylenedioxythiophene) can be firmly coated on the surface of the hollow microsphere copper cobalt sulfide, thereby effectively preventing poly (3,4-ethylenedioxythiophene) from agglomerating during the polymerization process. All of these can improve the specific capacitance of poly (3,4-ethylenedioxythiophene).

[0014] (3) The copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite material prepared by the present invention has a high specific capacitance and excellent electrochemical cycle stability. The supercapacitor prepared by using it as an electrode material has a specific capacitance of 198-223 F / g, 182-204 F / g, 171-189 F / g and 162-178 F / g at charge and discharge current densities of 1 A / g, 2 A / g, 4 A / g and 8 A / g, respectively. After 2000 cycles, the capacitance retention rate reaches 82.4-87.1%, thus having significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The X-ray diffraction spectrum of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in Example 1;

[0016] Figure 2 This is a transmission electron microscope image of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in Example 1;

[0017] Figure 3 The X-ray diffraction spectrum of the copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite material prepared in Example 1;

[0018] Figure 4 This is an infrared spectrum of the copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite material prepared in Example 1;

[0019] Figure 5 This is a scanning electron microscope image of the copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite material prepared in Example 1;

[0020] Figure 6 This is a scanning electron microscope image of the poly (3,4-ethylenedioxythiol) electrode material prepared in Comparative Example 1;

[0021] Figure 7 This is a scanning electron microscope image of the copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0022] The preparation of a copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite electrode material comprises the following steps:

[0023] (1) 0.5-1 g of copper nitrate trihydrate, 1-3 g of cobalt nitrate hexahydrate, 0.5-2 g of thioacetamide and 1-2 g of 3,4-ethylenedioxythiophene were added to a mixed solvent of 300-500 mL of ethylene glycol / ethanol (1:2-2:1, v / v), and mechanically stirred for 30-60 min at room temperature, and then ultrasonically mixed for 30-60 min. The resulting mixture was then transferred to a high-pressure reactor and reacted at 160-200 °C for 8-12 h. The mixture was then cooled, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material.

[0024] (2) 1-3 g of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in step (1) is added to 50-100 mL of deionized water, and mechanically stirred for 30-60 min at room temperature, and then ultrasonically dispersed for 1-2 h. Then, 1-6 g of 3,4-ethylenedioxythiophene is added, and mechanically stirred for 30-60 min, and then ultrasonically dispersed for 1-2 h. Then, 50-100 mL of ammonium persulfate hydrochloric acid solution (containing 0.5 mol / L ammonium persulfate and 0.2 mol / L hydrochloric acid) is added dropwise to the mixed dispersion at a rate of 10-20 drops / min, and mechanically stirred for 12-36 h at room temperature. After precipitation with methanol, filtration, washing, and vacuum drying, the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material is obtained.

[0025] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0026] Example 1

[0027] (1) 0.75 g of copper nitrate trihydrate, 2 g of cobalt nitrate hexahydrate, 1 g of thioacetamide and 1.5 g of 3,4-ethylenedioxythiophene were added to 400 mL of a mixed solvent consisting of ethylene glycol / ethanol (1:1, v / v), and mechanically stirred for 45 min at room temperature, and then ultrasonically mixed for 45 min. The resulting mixture was then transferred to a high-pressure reactor and reacted at 180 °C for 10 h. The mixture was then cooled, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material.

[0028] (2) 2 g of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in step (1) was added to 75 mL of deionized water. The mixture was first mechanically stirred for 45 min at room temperature and then ultrasonically dispersed for 1.5 h. Then, 3.5 g of 3,4-ethylenedioxythiophene was added. The mixture was first mechanically stirred for 45 min and then ultrasonically dispersed for 1.5 h. Then, 75 mL of ammonium persulfate hydrochloric acid solution (containing 0.5 mol / L ammonium persulfate and 0.2 mol / L hydrochloric acid) was added dropwise to the mixed dispersion at a rate of 15 drops / min. The mixture was mechanically stirred for 24 h at room temperature. The mixture was precipitated with methanol, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material.

[0029] Figure 1 This is an X-ray diffraction spectrum of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in this example. As shown in the figure, the diffraction peaks at 2θ of 12.5°, 26.5°, 31.2°, 37.9°, 49.9° and 54.7° are caused by the (200) crystal plane of 3,4-ethylenedioxythiophene and the (022), (113), (004), (115) and (044) crystal planes of copper cobalt sulfide, respectively, indicating that the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material was successfully prepared.

[0030] Figure 2 This is a transmission electron microscope image of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in this example. The image shows that the copper cobalt sulfide is a hollow microsphere structure with a thin shell layer, and poly 3,4-ethylenedioxythiophene is attached to the surface of the copper cobalt sulfide. This structure allows ions to diffuse quickly to all electrochemical reaction active sites, thereby improving the specific capacitance of the composite electrode material.

[0031] Figure 3 The X-ray diffraction spectrum of the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite material prepared in this example. The diffraction peaks at 2θ of 6.8°, 12.5°, 26.5°, 31.2°, 37.9°, 49.9° and 54.7° are caused by the (100) and (200) crystal planes of 3,4-ethylenedioxythiophene and the (022), (113), (004), (115) and (044) crystal planes of copper cobalt sulfide, respectively, indicating that the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite material was successfully prepared.

[0032] Figure 4 This is the infrared absorption spectrum of the copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite material prepared in this example. The figure shows that the infrared absorption spectrum at 1639 cm -1 、1355 cm -1 , 1211 cm -1 and 982 cm -1The absorption peaks of thiophene are derived from the stretching vibrations of C=C, CC, COC and CS on the thiophene ring. -1 A large number of characteristic absorption peaks of copper cobalt sulfide appeared, which indicated that the copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite material had been successfully prepared.

[0033] Figure 5 This is a scanning electron microscope image of the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite material prepared in this example. As shown in the figure, poly 3,4-ethylenedioxythiophene is evenly coated on the surface of the copper cobalt sulfide microspheres.

[0034] Example 2

[0035] (1) 0.5 g of copper nitrate trihydrate, 1 g of cobalt nitrate hexahydrate, 0.5 g of thioacetamide and 1 g of 3,4-ethylenedioxythiophene were added to a mixed solvent of 300 mL of ethylene glycol / ethanol (1:2, v / v), and mechanically stirred for 30 min at room temperature, and then ultrasonically mixed for 30 min. The resulting mixture was then transferred to a high-pressure reactor and reacted at 160 °C for 12 h. The mixture was then cooled, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material.

[0036] (2) 1 g of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in step (1) was added to 50 mL of deionized water, and mechanically stirred for 30 min at room temperature, and then ultrasonically dispersed for 1 h. Then, 1 g of 3,4-ethylenedioxythiophene was added, and mechanically stirred for 30 min, and then ultrasonically dispersed for 1 h. Then, 50 mL of ammonium persulfate hydrochloric acid solution (containing 0.5 mol / L ammonium persulfate and 0.2 mol / L hydrochloric acid) was added dropwise to the mixed dispersion at a rate of 10 drops / min, and mechanically stirred for 12 h at room temperature. After precipitation with methanol, filtration, washing, and vacuum drying, the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material was obtained.

[0037] Example 3

[0038] (1) 1 g of copper nitrate trihydrate, 3 g of cobalt nitrate hexahydrate, 2 g of thioacetamide and 2 g of 3,4-ethylenedioxythiophene were added to 500 mL of a mixed solvent consisting of ethylene glycol / ethanol (2:1, v / v). The mixture was first mechanically stirred for 60 min at room temperature and then ultrasonically mixed for 60 min. The resulting mixture was then transferred to a high-pressure reactor and reacted at 200 °C for 8 h. The mixture was then cooled, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material.

[0039] (2) 3 g of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in step (1) was added to 100 mL of deionized water, and mechanically stirred for 60 min at room temperature, and then ultrasonically dispersed for 2 h. Then, 6 g of 3,4-ethylenedioxythiophene was added, and mechanically stirred for 60 min, and then ultrasonically dispersed for 2 h. Then, 100 mL of ammonium persulfate hydrochloric acid solution (containing 0.5 mol / L ammonium persulfate and 0.2 mol / L hydrochloric acid) was added dropwise to the mixed dispersion at a rate of 20 drops / min, and mechanically stirred for 36 h at room temperature. After precipitation with methanol, filtration, washing, and vacuum drying, the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material was obtained.

[0040] Comparative Example 1

[0041] 3.5 g of 3,4-ethylenedioxythiophene was added to 75 mL of deionized water, and mechanically stirred for 45 min at room temperature, and then ultrasonicated for 1.5 h to obtain a 3,4-ethylenedioxythiophene solution. 75 mL of ammonium persulfate hydrochloric acid solution (containing 0.5 mol / L ammonium persulfate and 0.2 mol / L hydrochloric acid) was added dropwise to the above solution at a rate of 15 drops / min, and mechanically stirred for 24 h at room temperature. After methanol precipitation, filtration, washing and vacuum drying, poly (3,4-ethylenedioxythiophene) was obtained.

[0042] Figure 6 This is a scanning electron microscope photo of the poly (3,4-ethylenedioxythiophene) prepared in this comparative example. The figure shows that the poly (3,4-ethylenedioxythiophene) has a block-like and stacked morphology, which is not conducive to the contact between the poly (3,4-ethylenedioxythiophene) and the electrolyte, and is not conducive to the insertion and extraction of ions, resulting in a lower specific capacitance of the poly (3,4-ethylenedioxythiophene).

[0043] Comparative Example 2

[0044] (1) 0.75 g of copper nitrate trihydrate, 2 g of cobalt nitrate hexahydrate and 1 g of thioacetamide were added to 400 mL of a mixed solvent consisting of ethylene glycol / ethanol (1:1, v / v). The mixture was first mechanically stirred for 45 min at room temperature and then ultrasonically mixed for 45 min. The resulting mixture was then transferred to a high-pressure reactor and reacted at 180 °C for 10 h. The mixture was then cooled, filtered, washed and vacuum dried to obtain copper cobalt sulfide.

[0045] (2) 2 g of copper cobalt sulfide was added to 75 mL of deionized water. The mixture was first mechanically stirred for 45 min at room temperature and then ultrasonically dispersed for 1.5 h. Then, 3.5 g of 3,4-ethylenedioxythiophene was added. The mixture was first mechanically stirred for 45 min and then ultrasonically dispersed for 1.5 h. Then, 75 mL of ammonium persulfate hydrochloric acid solution (containing 0.5 mol / L ammonium persulfate and 0.2 mol / L hydrochloric acid) was added dropwise to the mixed dispersion at a rate of 15 drops / min. The mixture was mechanically stirred for 24 h at room temperature. The mixture was precipitated with methanol, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material.

[0046] Figure 7 This is a scanning electron microscope photo of the copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite electrode material prepared in this comparative example. The figure shows that the poly (3,4-ethylenedioxythiophene) coated on the surface of the copper cobalt sulfide microspheres has a partial agglomeration phenomenon.

[0047] The materials prepared in the examples and comparative examples were mixed with acetylene carbon black and polyvinylidene fluoride in a weight ratio of 80:15:5, and then evenly coated on a stainless steel mesh as a working electrode, a platinum wire as a counter electrode, a saturated calomel electrode as a reference electrode, and a 1 mol / L sulfuric acid aqueous solution as an electrolyte. The specific capacitance of the product was tested by a constant current charge and discharge method, and the electrochemical cycle stability of the product was tested by cyclic voltammetry, wherein the voltage range was -0.2 V to 0.8 V and the scan rate was 100 mV / s. The test results are shown in Table 1.

[0048] Table 1 Performance test results

[0049]

[0050] From the results in Table 1, it can be seen that the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material is first prepared by a solvothermal method, and then the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material is prepared by using it as a carrier and 3,4-ethylenedioxythiophene as a monomer through oxidative polymerization. The composite material has a higher specific capacitance and better cycle stability, and is more suitable for use as an electrode material for supercapacitors.

[0051] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite electrode material, characterized in that: First, copper nitrate trihydrate, cobalt nitrate hexahydrate, thioacetamide and 3,4-ethylenedioxythiophene are used as raw materials to prepare a copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material by a solvent thermal method, and then the obtained copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material is used as a carrier, 3,4-ethylenedioxythiophene is used as a monomer, and ammonium persulfate is used as an oxidant to obtain the composite electrode material through an oxidative polymerization reaction; It includes the following steps: (1) 0.5-1 g of copper nitrate trihydrate, 1-3 g of cobalt nitrate hexahydrate, 0.5-2 g of thioacetamide and 1-2 g of 3,4-ethylenedioxythiophene were added to 300-500 mL of a mixed solvent, and the mixture was first mechanically stirred for 30-60 min at room temperature, and then ultrasonically mixed for 30-60 min. The resulting mixture was then transferred to a high-pressure reactor and reacted at 160-200 °C for 8-12 h. The mixture was then cooled, filtered, washed and vacuum dried to obtain a copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material. (2) 1-3 g of the copper cobalt sulfide / 3,4-ethylenedioxythiophene composite material prepared in step (1) is added to 50-100 mL of deionized water, and mechanically stirred for 30-60 min at room temperature, and then ultrasonically dispersed for 1-2 h, and then 1-6 g of 3,4-ethylenedioxythiophene is added, and mechanically stirred for 30-60 min, and then ultrasonically dispersed for 1-2 h, and then 50-100 mL of ammonium persulfate hydrochloric acid solution is added dropwise to the mixed dispersion at a rate of 10-20 drops / min, and mechanically stirred for 12-36 h at room temperature, and precipitated with methanol, filtered, washed, and vacuum dried to obtain the copper cobalt sulfide / poly 3,4-ethylenedioxythiophene composite electrode material; The mixed solvent in step (1) is prepared by mixing ethylene glycol and ethanol in a volume ratio of 1:2 to 2:1; In the ammonium persulfate hydrochloric acid solution of step (2), the concentration of ammonium persulfate is 0.5 mol / L, the concentration of hydrochloric acid is 0.2 mol / L, and the solvent is deionized water.

2. A copper cobalt sulfide / poly (3,4-ethylenedioxythiophene) composite electrode material prepared by the method as claimed in claim 1.

Citation Information

Patent Citations

  • Method for preparing NiCo2O4 composite electrode material coated with conducting polymer

    CN104143450A

  • Preparation method of poly-3, 4-ethylenedioxythiophene / molybdenum disulfide / graphene composite material

    CN112185711A